2023
DOI: 10.1007/s00259-023-06339-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of an artificial intelligence-based tool in [18F]FDG PET/CT for the assessment of bone marrow involvement in multiple myeloma

Abstract: Purpose [18F]FDG PET/CT is an imaging modality of high performance in multiple myeloma (MM). Nevertheless, the inter-observer reproducibility in PET/CT scan interpretation may be hampered by the different patterns of bone marrow (BM) infiltration in the disease. Although many approaches have been recently developed to address the issue of standardization, none can yet be considered a standard method in the interpretation of PET/CT. We herein aim to validate a novel three-dimensional deep learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…2 ). Deep learning-based tools for automated TMTV delineation might be a faster tool to more accurately delineate [ 18 F]FDG-positive tumor burden [ 41 ]. Sachpekidis et al showed that the TMTV obtained using a deep learning–based delineation method in previously untreated MM patients was significantly correlated with BM plasma cell infiltration and was associated with PFS and OS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Deep learning-based tools for automated TMTV delineation might be a faster tool to more accurately delineate [ 18 F]FDG-positive tumor burden [ 41 ]. Sachpekidis et al showed that the TMTV obtained using a deep learning–based delineation method in previously untreated MM patients was significantly correlated with BM plasma cell infiltration and was associated with PFS and OS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DL-based approach has demonstrated significant, moderate, positive correlations between bone marrow plasma cell infiltration and plasma β2-microglobulin levels, as well as with the automated quantitative PET/CT parameters, MTV and TLG [13].…”
Section: Pioneering Artificial Intelligence In the Medical Specialtie...mentioning
confidence: 96%
“…The consistency between different observers when interpreting PET/CT scans could be impacted by the diverse patterns of bone marrow infiltration typical of the disease [65]. To tackle this issue, a group of scientists aimed to validate a new three-dimensional deep learning tool [65]. The proposed automated method for evaluating bone marrow…”
Section: Ai For Pet Quantificationmentioning
confidence: 99%
“…The consistency between different observers when interpreting PET/CT scans could be impacted by the diverse patterns of bone marrow infiltration typical of the disease [65]. To tackle this issue, a group of scientists aimed to validate a new three-dimensional deep learning tool [65]. The proposed automated method for evaluating bone marrow metabolism begins with the segmentation of the skeleton, which is based on CT data (Figure 15) [65].…”
Section: Ai For Pet Quantificationmentioning
confidence: 99%
See 1 more Smart Citation